Europe agreements and trade balance: Evidence form four new EU members - Guglielmo Maria Caporale; Christophe Rault; Robert Sova; Anamaria Sova (Institute for the Study of Labor (IZA), 2011)
This paper analyses the trade balance effects of Europe agreements (EA) between the EU-15 and four new EU members from Central and Eastern Europe (CEEC-4) using both static and dynamic panel data approaches. Specifically, the system Generalized Method of Moments (GMM, Blundell and Bond, 1998) and recently developed econometric methods such as the Correlated Common Estimation Pooled - Hausman-Taylor (CCEPHT, Serlenga and Shin, 2007) are applied to analyse the effects of the agreement variable. Our estimation results indicate a positive and significant impact of EA on trade flows. However, there is an asymmetric impact of the agreement variable on the trade balance, exports and imports being affected in different ways, which results in a trade balance deficit in the CEEC-4.
urn:nbn:de:101:1-201105173199
Keywords: E61; F13; F15; C25; 330; regionalisation; trade flows; trade balance; panel data methods